Measurement of fundamental chromatography parameters in conventional and split‐flow comprehensive two‐dimensional gas chromatography‐mass spectrometry: A focus on the importance of second‐dimension injection efficiency. Issue 1 (4th October 2012) - Tranchida, Peter Quinto; Zoccali, Mariosimone; Franchina, Flavio Antonio; Dugo, Paola; Mondello, Luigi; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The present manuscript reports a comparative study between conventional and split‐flow comprehensive GC×GC‐MS. Conventional GC×GC‐MS was performed by using a single GC oven, and with a widely employed apolar (30 m × 0.25 mm id)‐polar (1 m × 0.10 mm id) column combination. Split‐flow GC×GC‐MS experiments were carried out by using the same first and second analytical columns, and by diverting part of the primary‐capillary flow to waste, via a waste line. The latter was located at the conjunction point between the two dimensions. The measurement of fundamental gas chromatography parameters (efficiency, resolution), in both dimensions and under different experimental conditions, enabled the attainment of detailed information related to GC×GC‐MS method optimization. Finally, the results derived from the present investigation highlight an important GC×GC issue, namely the efficiency of band reinjection onto the second‐dimension capillary.